Optimal Taxation of Capital in the Presence of Declining Labor Share - Orhan Erem Atesagaoglu; Hakki Yazici (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We analyze the implications of the decline in labor's share in national income for optimal Ramsey taxation. It is optimal to accompany the decline in labor share by raising capital taxes only if the labor share is falling because of a decline in competition or other mechanisms that raise the share of pure profits. This result holds under various alternative institutional arrangements that are relevant for optimal taxation of capital income. A quantitative application to the U.S. economy shows that soaring profit shares since the 1980's can justify a significantly increasing path of capital income taxes.
Keywords: E60; E61; E62; 330; capital income tax; labor share; profit share; market power